Migrating Lateral Ventricle Choroid Plexus Cyst into the Fourth Ventricle Causing Acute Hydrocephalus - Carter, Lacey M.; Cornwell, Benjamin; Gross, Naina L. (Journal of Pediatric Neurology, 2021)
Choroid plexus cysts consist of abnormal folds of the choroid plexus that typically resolve prior to birth. Rarely, these cysts persist and may cause outflow obstruction of cerebrospinal fluid. In this article, we presented a 5-month-old male child patient who presented with lethargy, vomiting, and a bulging anterior fontanelle. Magnetic resonance imaging showed one large choroid plexus cyst had migrated from the right lateral ventricle through the third ventricle and cerebral aqueduct into the fourth ventricle causing outflow obstruction. The cyst was attached to the lateral ventricle choroid plexus by a pedicle. The cyst was endoscopically retrieved from the fourth ventricle intact and then fenestrated and coagulated along with several other smaller cysts. Histologic examination confirmed the mass was a choroid plexus cyst. The patient did well after surgery and did not require any cerebrospinal fluid diversion. Nine months after surgery, the patient continued to thrive with no neurological deficits. This case is the first we have found in the literature of a lateral ventricular choroid plexus cyst migrating into the fourth ventricle and the youngest of any migrating choroid plexus cyst. Only three other cases of a migrating choroid plexus cyst have been documented and those only migrated into the third ventricle. New imaging advances are making these cysts easier to identify, but may still be missed on routine sequences. High clinical suspicion for these cysts is necessary for correct treatment of this possible cause of hydrocephalus.
Keywords: choroid plexus cyst; hydrocephalus; endoscopy; case report